Dilemma zone conflicts at isolated intersections controlled with fixed-time and vehicle actuated traffic signal systems - Che Puan, Othman (IJCEE Pub., 2010)

(untitled)
Installation of traffic signal control system at relatively high traffic volume intersections is expected to safeguard drivers at such intersections by providing a clear definition of right–of–way to drivers. However, a particular operational issue is the existence of dilemma zone conflicts if the type traffic signal system installed is not properly selected and designed. The problem is critical for isolated intersections on relatively high speed road sections. This paper describes result of a study carried out to investigate the existence of dilemma zone conflicts at isolated intersections installed with various types of traffic signal control systems. Three indicators of dilemma zone conflicts considered in the analysis are (i) stop abruptly; (ii) accelerate through amber period; and (iii) red–light running. Data pertaining to the analysis of dilemma zone conflicts was collected at eight isolated intersections with different types of traffic signal control systems using a video–recording technique. The data includes vehicles’ approaching speed, distance from the stop line at the onset of amber, the decision made by the drivers at onset of amber as well as the types of vehicles driven. The result shows that relatively large proportion of drivers did not willing to stop at onset of amber signal. A vehicle–actuated traffic signal system appears to perform better compared to other types of system in terms of reduction in dilemma zone conflicts at isolated signalized intersections.